Remembering 1965: Trauma, Silence, And Counter-Memory In Indonesian Historical Prose - Deni Prastiono (Politeknik Siber Cerdika Internasional, 2025)
This study examines Indonesian historical prose addressing the 1965 events, focusing on the representation of trauma, narrative silence, and counter-memory. Utilizing a qualitative research design, the study analyzes selected literary texts through thematic, narrative, and interpretive approaches. Findings reveal that trauma is depicted both individually and collectively, conveyed through fragmented narratives, flashbacks, episodic storytelling, and symbolic imagery. Narrative silence emerges as a deliberate literary strategy, employing omissions, ellipses, and ambiguous endings to convey the unspeakable nature of violence while inviting readers’ interpretive engagement. Counter-memory functions as a critical mechanism to resist hegemonic historical narratives, highlighting marginalized voices, intergenerational memory, and alternative perspectives. The interaction of trauma, silence, and counter-memory demonstrates that literature does not merely reflect historical events but actively mediates memory, ethical reflection, and social consciousness. The study also shows that literary strategies provide insight into the sociopolitical context, ethical dilemmas, and cultural constraints surrounding the representation of sensitive historical events. Practical implications include the integration of historical prose into education, literary practice, and public discourse to promote critical engagement, social reconciliation, and recognition of suppressed histories. Despite limitations related to sampling, scope, and interpretive subjectivity, this research contributes to interdisciplinary understanding of how literature functions as both an ethical witness and a medium for historical reconstruction. The findings underscore the role of narrative form, symbolism, and thematic strategies in preserving collective memory and challenging dominant historical narratives.